2017
DOI: 10.1371/journal.pone.0182019
|View full text |Cite
|
Sign up to set email alerts
|

The phosphodiesterase inhibitor, ibudilast, attenuates neuroinflammation in the MPTP model of Parkinson’s disease

Abstract: Background/AimsSince the degeneration of the nigrostriatal dopaminergic pathway in Parkinson’s disease (PD) is associated with the inflammation process and decreased levels of cyclic nucleotides, inhibition of up-regulated cyclic nucleotide phosphodiesterases (PDEs) appears to be a promising therapeutic strategy. We used ibudilast (IBD), a non-selective PDE3,4,10,11 inhibitor, due to the abundant PDE 4 and 10 expression in the striatum. The present study for the first time examined the efficacy of IBD in the 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 63 publications
1
31
0
Order By: Relevance
“…Qin, Zhang, Cao, Loh, and Cheng () reported that higher peripheral concentrations of IL‐1β, IL‐2, IL‐6, and TNF‐α are observed in patients with PD, providing the clinical evidence that PD is accompanied by neuroinflammation. In addition, the expression of TNF‐α and IL‐1β was statistically increased in the MPTP‐based mouse models of PD (Schwenkgrub et al, ). In the present study, we showed that MPP + significantly induced the expression of IL‐6, IL‐1β, and TNF‐α in BV‐2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Qin, Zhang, Cao, Loh, and Cheng () reported that higher peripheral concentrations of IL‐1β, IL‐2, IL‐6, and TNF‐α are observed in patients with PD, providing the clinical evidence that PD is accompanied by neuroinflammation. In addition, the expression of TNF‐α and IL‐1β was statistically increased in the MPTP‐based mouse models of PD (Schwenkgrub et al, ). In the present study, we showed that MPP + significantly induced the expression of IL‐6, IL‐1β, and TNF‐α in BV‐2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, as far as we know, the efficacy of Eritoran has never been tested in PD [ 128 ]. Ibudilast is a cyclic nucleotide phosphodiesterase inhibitor as well as a TLR4 antagonist which is currently used as a bronchodilator, vasodilator and anti-inflammatory agent for the treatment of asthma, post-stroke dizziness and ocular allergies in Japan and other Asian countries [ 129 ]. Considering its documented ability on up-regulating the anti-inflammatory cytokines (i.e., IL-10, IL-4) and promoting the production of neurotrophic factors (i.e., GDNF, NGF, NT-4), it has been recently tested in an animal model of PD.…”
Section: Potential Therapeutic Strategiesmentioning
confidence: 99%
“…Ibudilast showed an anti-inflammatory response via the modulation of glial cell activity, attenuation of TNF-α expression and induction of GDNF. However, these ibudilast-mediated beneficial events were not a sufficient protection in the acute phase of injury [ 129 ]. Anti-TLR2 antibodies have been tested in clinical studies for treating severe sepsis and inflammation.…”
Section: Potential Therapeutic Strategiesmentioning
confidence: 99%
“…Additionally, the MIF inhibitor 4-IPP, which does disrupt the interaction of MIF with CD74 showed no efficacy ( Figure 4A) 43 . While ibudilast has been shown to inhibit the interaction of MIF and CD74, there are also reports that it is a phosphodiesterase inhibitor 53,54 . To assess specificity, we compared Ibudilast at 100 µM and 200 µM to Rolipram, which is a known specific and potent phosphodiesterase inhibitor at the same concentrations ( Figure 4B) 55…”
Section: Mif Inhibitor Screening Identified the Mif/cd74 Interaction mentioning
confidence: 99%